2014
DOI: 10.1186/preaccept-1248701577135074
|View full text |Cite|
|
Sign up to set email alerts
|

The role of microRNA-133b and its target gene FSCN1 in gastric cancer

Abstract: Background: Increasing evidences have documented that microRNAs (miRNAs) act as oncogenes or tumor suppressors in gastric cancer (GC). In this study, we aimed to investigate the expression of miR-133b in a large number of GC samples and elucidate its role in GC carcinogenesis and the detailed mechanism. Methods: We used Taqman probe stem-loop real-time PCR to accurately measure the levels of miR-133b in 100 pairs of gastric cancer tissues and the adjacent non-neoplastic tissues. miR-133b mimics were overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 37 publications
4
21
0
Order By: Relevance
“…Therefore, FSCN1 is involved in the regulation of cell motility. In the present study, FSCN1 was notably upregulated in NSCLC cell lines, and the overexpression of FSCN1 reversed the suppressive effect of miR-133b overexpression on NSCLC cell migration and invasion, suggesting that FSCN1 plays an oncogenic role in NSCLC (23)(24)(25). Similar findings have also been reported in other types of human cancers; for instance, the knockdown of FSCN1 was found to inhibit the proliferation and invasion of gastric cancer cells (23).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, FSCN1 is involved in the regulation of cell motility. In the present study, FSCN1 was notably upregulated in NSCLC cell lines, and the overexpression of FSCN1 reversed the suppressive effect of miR-133b overexpression on NSCLC cell migration and invasion, suggesting that FSCN1 plays an oncogenic role in NSCLC (23)(24)(25). Similar findings have also been reported in other types of human cancers; for instance, the knockdown of FSCN1 was found to inhibit the proliferation and invasion of gastric cancer cells (23).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, FSCN1 was notably upregulated in NSCLC cell lines, and the overexpression of FSCN1 reversed the suppressive effect of miR-133b overexpression on NSCLC cell migration and invasion, suggesting that FSCN1 plays an oncogenic role in NSCLC (23)(24)(25). Similar findings have also been reported in other types of human cancers; for instance, the knockdown of FSCN1 was found to inhibit the proliferation and invasion of gastric cancer cells (23). In addition, the inhibition of FSCN1 resulted in a reduced number of filopodia, an altered glioma cell shape, and inhibited the migration and invasion of glioma cells (24).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Of particular importance, our microarrays revealed an up-regulation of FSCN1 transcripts in XIAP 3′UTR cells. Several studies have reported that FSCN1 is highly expressed in malignant tumors, and is associated with increased cell motility and aggressive behavior of tumors [29, 3739]. This is similar to the findings in breast cancer, where overexpression of FSCN1 was correlated with invasion and predicts poor survival [30].…”
Section: Discussionsupporting
confidence: 75%
“…miRNAs regulate gene expression via post-transcriptional gene silencing of messenger RNAs (mRNAs), potentially leading to mRNA degradation, with consequent inhibition of gene translation [12]. In gastric cancer, miR-133b acts as a tumor suppressor and negatively regulates FSCN1 expression [13]. Restoring the expression of miR-133b can inhibit the growth and invasion of colorectal cancer cells via directly targeting EGFR [14].…”
Section: Introductionmentioning
confidence: 99%